PROCESS AND SYSTEMS Unlocking the benefits of the Baveno VI guidance when screening for varices: an audit of clinical practice across London. Issue 1 (2022) - Colwill, Michael; Lake, A Luke; El-Sayed, B Ahmed; King, C Jonathan; Kader, D Rawen; Shakweh, E Eathar
No abstract available